NON-VIOLENT CAUSES OF DEATH IN CHILDHOOD - FORENSIC ASPECTS AND STATISTICAL ANALYSIS OF THE PROBLEM - Dimitar Nikolov; Teodora Kiryakova; Biliana Mileva; Alexandar Alexandrov (Science & Research, 2019)

(untitled)
Introduction: Good health is a prerequisite for personal and social well-being. Child death largely reflects the impact of social conditions on the health of the population and serves as a criterion for assessing the quality of therapeutic and prophylactic activities in the country. Materials and Methods: We performed a complete forensic autopsy, histological examination, chemical analysis of blood and urine samples for each of the cases investigated, with a subsequent statistical analysis of the results obtained. Results: In the Department of Forensic Medicine and Deontology, Medical University of Sofia, for the period 2006 - 2015 a total of 10443 autopsy of deceased on the territory of Sofia-city and Sofia-region were performed, out of which 292 were cases of people under the age of 18. In about a third of them the cause of death was a result of a disease. Discussion: In infancy, the most common nonviolent causes of death are those of the respiratory system, followed by diseases of the nervous system, the cardiovascular system, genetic, infectious, malignant diseases and conditions. In some cases, no significant clinical manifestations have been identified, requiring forensic autopsies to clarify the cause of death and the exclusion of a violent one as well as improper treatment, which is why the diagnosis is often histological in these cases. Conclusion: Prophylaxis and prevention of congenital diseases, as well as the early detection and treatment of acquired diseases, are the basis of reducing the mortality in children. The joint action of parents, doctors and the health system is the basis for better and more effective measures to preserve the lives and health of children in each age group.